Comparison of Perceived Stress Levels among Private and Government Hospital Nurses - Ghazanfar Abbas; Aqsa Sajjad; Faisal Nadeem; Warda Tu Nisa; Jerry Zahid (Research Journal of Psychology, 2025)
Introduction: Nurses play a crucial role in healthcare but often encounter stressors that impact both their well-being and the quality of patient care. These stressors range from emotional strain and interpersonal conflicts to heavy workloads and extended hours. The stress range from moderate to severe level among European nurses whereas Asian nurses have higher stress level particularly about 80% nurses in Pakistan experience moderate stress level. Objective: This study aims to explore the stress levels among nurses working in government and private hospitals in Pakistan. Methodology: A cross-sectional design was used to collect data through self-administered questionnaires distributed to registered nurses at various government and private hospitals. Perceived Stress Scale (PSS-10) was utilized to identify key stressors affecting nurse’s performance. Descriptive and inferential statistical methods were utilized to compare stress levels between nurses in different hospital settings. Results: A total of 149 nurses, 52 from government hospitals and 97 from private hospitals were recruited. Private-sector nurses reported significantly higher stress levels (M = 22.6 ± 3.8) compared to government hospital nurses (M = 19.8 ± 4.2, t = 4.23, p < 0.001). Key stressors included workload pressures (65% in private hospitals) and resource shortages (55% in government hospitals). Male nurses exhibited higher stress levels (M = 21.9 ± 4.1) compared to females (M = 19.6 ± 3.7, t = 2.45, p = 0.015). Age was positively correlated with stress (r = 0.36, p < 0.01), while years of experience showed no significant correlation (r = 0.12, p = 0.14). Conclusion: The study reveals significant differences in stress levels between nurses in government and private hospitals, with workload being a major factor in private hospitals and resource shortages in government hospitals. Gender differences and the impact of age on stress were also observed. The findings suggest the need for targeted interventions to improve nurse well-being and enhance patient care quality in Pakistan’s healthcare sector.